Correlations between morphological traits and catechin content on tea (Camellia sinensis (L.) O. Kuntze) - Syahrian, Heri; Carsono, Nono; Rostini, Neni; Rahadi, Vitria Puspitasari; Sriyadi, Bambang (Research Institute for Tea and Cinchona, 2015)
Catechin content in tea plant is a major character in tea breeding program for a healthy beverage. A tea breeding program for high catechin content maybe will performed by indirect selecting a trait or traits that signiÂficantly correlated with high catechin content. This research was performed to identify morÂphological traits which maybe significantly correlated with high catechin content in tea plant. A randomized complete block design with three replications was used in this experiment using 10 selected clones. The experiment was performed in Gambung Experimental Station ot the Research Institute for Tea and Cinchona, Gambung, West Java. Catechin content, triÂchoma density of young leaves, weight of p+2, size of mother leaves, chlorophyll content of mother leaf, stomatal density of mother leaf, mother leaf thickness, and mother leaf angle, were measured. The results indicated that stomatal density and mother leaf angle were significantly correlated. Based on path analysis indirect selection for high catechin content could be performed by selecting stomatal density considering to trichoma density, mother leaf angle and chlorophyll content. In addition, indirect selection for high catechin content could be performed by selecting other leaf angle independently without considering other morphological traits.